A selection of AKARI FIS BSC extragalactic objects. Issue Volume 11:Issue S319(2015) (17th August 2016) - Marton, G.; Tóth, L.V.; Balázs, L. G.; Zahorecz, S.; Bagoly, Z.; Horváth, I.; Rácz, I. I.; Nagy, A.
Abstract: The point sources in the Bright Source Catalogue (BSC) of the AKARI Far–Infrared Surveyor (FIS) were classified based on their far–IR and mid–IR fluxes and colours using Quadratic Discriminant Analysis method (QDA) and Support Vector Machines (SVM). The reliability of our results show that we can successfully separate galactic and extragalactic AKARI point sources in the multidimensional space of fluxes and colours. However, differentiating among the extragalactic sub–types needs further information.